Keterampilan Mengadakan Variasi - Fitri Maharani Siagian; Nur Aliyah; Riska Yulia; Kholidah Nur (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
The skill of providing variety is one of the important competencies in early childhood learning which aims to create a fun, interesting and effective learning atmosphere. This research aims to analyze the application of variation skills in the early childhood learning process and its impact on children's interest and participation. The research used a descriptive qualitative approach with observation, interviews and documentation methods on teachers and students at an early childhood education institution. The research results show that variations in learning methods, media and interactions significantly increase children's involvement in learning activities. Teachers who are able to consistently provide variation also encourage the development of children's cognitive, social-emotional and motoric aspects. This research recommends special training for early childhood educators to improve skills in providing variation as the main strategy in learning.